Determinant of The Corporate Social Responsibility Disclosure - Uun Sunarsih; N. Nurhikmah (ETIKONOMI, 2017)
Corporate Social Responsibility (CSR) has a very important role for the company and now become an obligation for every company. The purpose of this study examined the effect of institutional ownership, board of commissioners, profitability and size on CSR disclosure. This research conducted at mining manufacturing companies listed in Indonesia Stock Exchange period 2013-2014 and obtained 76 sample companies. The method used is multiple regression analysis. The result showed only institutional ownership affecting CSR disclosure. This suggests institutional ownership structure can act in monitoring the company. Independent board has not effected on CSR, it failed to monitor the actions of top management. Profitability has not effected on the disclosure of CSR, it enabled the company to have two perspectives on CSR. The most companies view CSR as a deduction from earnings. CSR disclosure has not affect the size of the CSR disclosure area.DOI: 10.15408/etk.v16i2.5236